Comparison of internal fit of metal‐ceramic crowns in CAD/CAM and lost‐wax techniques in all fabrication stages through replica weighting, triple scanning, and scanning electron microscope - Sina Mohammadi Sadr; Elham Ahmadi; Masoumeh Hasani Tabatabaei; Saba Mohammadi; Faezeh Atri (Wiley, 2022)
Abstract Objectives Restoration fit is one of the prerequisites of clinical durability. It is controversial as to whether computer‐assisted design/computer‐aided milling (CAD/CAM) or lost‐wax fabrication methods result in more fit metal‐ceramic crowns. This in‐vitro study was conducted to examine the internal fit of porcelain fused to metal crowns fabricated using CAD/CAM and lost‐wax techniques during fabrication stages (framework, porcelain, cementation) through digital triple scanning, replica weighting, and observation with electron microscopy. Material and methods Twenty uniform resin dies of prepared first maxillary molars were randomly divided into two groups according to the fabrication technique: lost wax and CAD/CAM. The internal fit was measured in all steps of completing the crowns (framework, porcelain, and cementation) using different methods, including triple scanning, replica weighting, and scanning electron microscopy. The data were statistically analyzed using t test, Pearson, and repeated measures analysis of variance (α = .05). Results Triple scanning revealed no difference in the internal fit of CAD/CAM and lost‐wax groups in all the fabrication steps (p > .05). The replica weighting method showed no difference between groups in the framework step (p > .05), while the internal fit was significantly better in the CAD/CAM group after porcelain application (p < .05). After cementation, electron microscopy measurements showed no difference between CAD/CAM and lost wax groups (p > .05). The Pearson correlation test showed no significant correlation between electron microscopy, replica weighing, and triple scanning methods (p > .05). Conclusion According to scanning electron microscopy as the superior evaluation method, the internal fit of cobalt-chrome PFM crown of both CAD/CAM and lost wax groups was within the acceptable clinical range and there was no significant difference between them. Triple scanning revealed no difference in the internal fit of framework and porcelain steps but a better fit after cementation. According to replica weighting, the internal fit in the porcelain step was higher than the framework.